2014
DOI: 10.1021/ic402613z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Studies on the Reaction of the Vitamin B12 Complex Aquacobalamin with the HNO Donor Angeli’s Salt: Angeli’s Salt and HNO React with Aquacobalamin

Abstract: We report the first studies on the reaction between an HNO donor compound and vitamin B12 complexes. Kinetic and mechanistic studies have been carried out on the reaction between the vitamin B12 derivative aquacobalamin (H2OCbl(+)/HOCbl; pKa = 7.8) and the HNO donor Angeli's salt. Studies were carried out with aquacobalamin in excess, since nitrite also reacts with aquacobalamin to form nitrocobalamin (NO2Cbl). At pH <9.90 aquacobalamin reacts directly with the monoprotonated form of Angeli's salt, HN2O3(-), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…Finally, note that Cbl(II) does not react to any significant extent with cyanide (Figure S6, Supporting Information). The results of these multiple experiments do not support a Cbl(III) intermediate for the reaction of Cbl(II) with AS, despite the fact that Cbl(III) reacts rapidly with AS with a 1:1 stoichiometry to form NOCbl 27. In addition, data simulation using Pro‐Kineticist software also suggest that Cbl(III) is not the intermediate in the reaction between Cbl(II) and AS (data not shown).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Finally, note that Cbl(II) does not react to any significant extent with cyanide (Figure S6, Supporting Information). The results of these multiple experiments do not support a Cbl(III) intermediate for the reaction of Cbl(II) with AS, despite the fact that Cbl(III) reacts rapidly with AS with a 1:1 stoichiometry to form NOCbl 27. In addition, data simulation using Pro‐Kineticist software also suggest that Cbl(III) is not the intermediate in the reaction between Cbl(II) and AS (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…Note that a Cbl(II)/HNO = 1:2 stoichiometry was also found for the nitrite‐free HNO donor Piloty's acid (unpublished results). Given that a substantial fraction of cob(III)alamin [Cbl(III)] exists as aquacobalamin [p K a (H 2 OCbl + ) = 7.834] and that independent experiments have shown that H 2 OCbl + reacts rapidly with AS to give NOCbl,27 this suggests that the Cbl(II) + AS reaction proceeds via a Cbl(III) intermediate. In order to probe this further, experiments were carried out in the presence of an efficient H 2 OCbl + trap cyanide, which reacts rapidly and essentially irreversibly with H 2 OCbl + to form cyanocobalamin [CNCbl; k f = 250 M –1 s –1 and K (CNCbl) ≥ 10 12 M –1 ] 35.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the recent literature [ 30 , 31 ] it is known that free · NO can be reduced by ascorbic acid to form HNO, which in turn can react with CblOH 2 to form CblNO. Brasch and coworkers [ 32 ] demonstrated that using Angeli’s salt (HN 2 O 3 − ) as source of HNO, the formation of CblNO can occur at pH > 10.8, where the rate-determining step is the release of HNO by Angeli’s salt, such that no mechanistic details about the mechanism of the reaction between CblOH 2 /CblOH and HNO/NO − could be revealed. At present, it is questionable whether further reduction of · NO to HNO and a direct reaction of CblOH 2 with HNO to form CblNO can account for the results presented in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Given that others have reported that the reaction between HNO and trialkylphosphines is not stoichiometric, the vitamin B 12 derivative hydroxycobalamin (HOCbl⋅HCl) was employed to determine the amount of HNO released. Under alkaline conditions HOCbl (red) reacts stoichiometrically with HNO (1:1) to produce orange nitroxylcobalamin, NOCbl . HOCbl does not react with NO .…”
Section: Methodsmentioning
confidence: 99%